Innovation, Research and Development and Capital Evaluation - Aldieri, Luigi (IntechOpen, 2022)
The role of innovation is becoming increasingly crucial in modern societies. In particular, investments in Research and Development represent an important tool for promoting innovation and for enhancing the capital invested in the market. By now, innovation is linked with different concepts, from entrepreneurship to sustainability, from economics to management. The analysis of the innovation process involves different skills to overcome the high degree of competitiveness and allow higher levels of profits. In the text, the interactions among innovation, entrepreneurship, and ecosystems are investigated. It is an attempt to prepare the theoretical bases to face in an appropriate way the transformations of modern economic and organizational systems and to suggest adequate support policies.